Kearifan Lokal Dalam Pengelolaan Hutan Adat Di Desa Rantau Kermas Kecamatan Jangkat Kabupaten Merangin - Tamami Tamami; Rikky Herdiyansyah (Universitas Jambi, 2022)
The law tradition of society is a community of people who conduct their daily lives very close to the nature environment, moreover in various of academic literature in the law tradition of society is often considered as part of dynamics nature environment, so the wisdom of law tradition society as part of life that really needs to be expressed.As general, this research to purposed analyze the local wisdom related with arrangement, usage, and protection of traditional forest in Rantau Kermas village, ex. Serampas clan, Jangkat Subdistrict. The research was conducted in the Rantau Kermas village, ex. Serampas clan used Snowball sampling method or Snowball sampling used informants by way of non- probability. The result of this research, it was shown in society life have many traditional knowledge that underlines the formation of one value in every day life. The knowledge passed down from one generation to generation with developed as balanced in interaction with environment. Related to this research have some conclusions in the management of traditional forest as follows : the local wisdom associated with traditional forest arrangement, the local wisdom asoociated with traditional forest usage, and the local wisdom associated with traditional forest protection.